LASER TUNNELING OF THE PANCREAS IN PATIENTS WITH CHRONIC FIBROSING PANCREATITIS - Zh. A. Revel-Muroz (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Laser tunneling of pancreas for stimulation of neoangiogenesis, regeneration and reverse of sclerotic changes was performed in 23 patients with fibrosclerotic pancreatitis. Twelve of them were men and eleven were women. The age of patients ranged from 23 to 71 years. All the patients had persistent pain and dyspeptic syndromes, with negligible effect on antispasmodics. Medical history of the disease was from 6 months to 15 years, the frequency of severe attacks requiring hospitalization was from 2 to 6 per year. The results of clinical trial testify for possibility of safe and. effective application of laser tunneling of pancreas in patients with chronic pancreatitis. One of the significant features of the operation was the pain relief and. life quality improvement in those patients.